Say's involvement in the 1819 French edition of Ricardo's Principles and the issue of rent. Issue 1 (2nd January 2017) - Depoortère, Christophe
Abstract: This paper focuses on Say's contribution to the first French edition of Ricardo's Principles and on the analytical consequences of his involvement on the issue of rent. Part one investigates the "story" of this edition. It stresses Say's friendship with the translator, his involvement in this publication and his attitude toward Ricardo. Part two analyses how elements from Say's thought were introduced into Ricardo's theory of rent through this edition. These elements conveyed ideas which were definitely at odds with Ricardo's theory and misrepresented Ricardo's true concept of differential rent which was central to his theory.